Sitagliptin reduces inflammation, fibrosis and preserves diastolic function in a rat model of heart failure with preserved ejection fraction - Esposito, Grazia (Br J Pharmacol, 2017)
BACKGROUND AND PURPOSE: Heart failure with preserved ejection fraction (HFpEF) is a systemic syndrome driven by co‐morbidities, and its pathophysiology is poorly understood. Several studies suggesting that dipeptidyl peptidase 4 (DPP4) might be involved in the pathophysiology of heart failure have prompted experimental and clinical investigations of DPP4 inhibitors in the cardiovascular system. Here we have investigated whether the DPP4 inhibitor sitagliptin affected the progression of HFpEF independently of its effects on glycaemia. EXPERIMENTAL APPROACH: Seven‐week‐old Dahl salt‐sensitive rats were fed a high‐salt diet for 5 weeks to induce hypertension. Then the rats continued with the high‐salt diet and were treated with either sitagliptin (10 mg·kg(−1)) or vehicle for the following 8 weeks. Blood pressure and cardiac function were measured in vivo. Histochemical and molecular biology analyses of myocardium were used to assay cytokines, fibrotic markers, DPP4 and glucagon‐like peptide‐1 (GLP‐1)/GLP‐1 receptor. KEY RESULTS: Treatment with sitagliptin attenuated diastolic dysfunction, reduced mortality and reduced cardiac DPP4 activity, along with increased circulating GLP‐1 and myocardial expression of GLP‐1 receptors. Myocardial levels of pro‐inflammatory cytokines (TNF‐α, IL‐6 and CCL2) were reduced. Sitagliptin treatment decreased the levels of endothelial NOS monomer, responsible for generation of ROS, while the amount of NO‐producing dimeric form increased. Markers of oxidative and nitrosative stress were decreased. Moreover, increased collagen deposition and activation of pro‐fibrotic signalling, inducing elevated myocardial stiffness, were attenuated by sitagliptin treatment. CONCLUSIONS AND IMPLICATIONS: Sitagliptin positively modulated active relaxation and passive diastolic compliance by decreasing inflammation‐related endothelial dysfunction and fibrosis, associated with HFpEF. LINKED ARTICLES: This article is part of a themed section on Targeting Inflammation to Reduce Cardiovascular Disease Risk. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.22/issuetoc and http://onlinelibrary.wiley.com/doi/10.1111/bcp.v82.4/issuetoc